Bilateral Knee Extensor Fatigue Modulates Force and Responsiveness of the Corticospinal Pathway in the Non-fatigued, Dominant Elbow Flexors - Šambaher, Nemanja; Aboodarda, Saied Jalal; Behm, David George (Frontiers in Human Neuroscience, 2016)
Exercise-induced fatigue affects muscle performance and modulates corticospinal excitability in non-exercised muscles. The purpose of this study was to investigate the effect of bilateral knee extensor fatigue on dominant elbow flexor (EF) maximal voluntary force production and corticospinal excitability. Transcranial magnetic, transmastoid electrical and brachial plexus electrical stimulation were used to investigate corticospinal, spinal, and muscle excitability of the dominant EF before and after a bilateral knee extensor fatiguing protocol or time matched rest period (control). For both sessions three stimuli were delivered every 1.5s during the three pre-test time points and during the 1st, 3rd, 6th, 9th and 12th post-test 5s EF isometric maximal voluntary contractions (MVC). In both conditions, Overall, EF MVC force (p< 0.001) decreased progressively from repetition #1 to #12 during the post-test MVC protocol. EF MVC force (p < 0.001, ES = 0.9, ∆ 10.3%) decrements were more pronounced in the knee extensor fatigue intervention condition. In addition, there were no significant differences between conditions for biceps brachii electromyographic (EMG) activity (p = 0.43), motor evoked potentials (MEP) amplitude (p=0.908) or MEP silent period (p=0.776). However, the fatigue condition exhibited a lower MEP/ cervico-medullary MEP (CMEP) ratio (p=0.042, ES=2.5, ∆25%) and a trend toward higher CMEP values (p=0.08, ES=0.5, ∆20.4%). These findings suggest that bilateral knee extensor fatigue can impair performance and modulate corticospinal excitability of the EF.